The Effects of Emotional vs. Logical Anti-Smoking Advertisements on Smoking Discouragement, Depression and Self-Esteem - L. Wilson, Andrew L. Wilson (International Journal of Psychosocial Rehabilitation, 2017)
The purpose of the study is to investigate if the effects of emotional anti-smoking advertisements can help discourage smoking over logical anti-smoking advertisements. Although research has proven that logical advertisements can be useful, the authors predict that emotional advertisements will be more effective because people are highly driven by emotional responses. However, if students feel depressioned or have low self-esteem after watching either of the two advertisements, then there could be a chance that they may not benefit from the full effects. The study employed a randomized controlled pretest-posttest group of 2nd year undergraduate students (n=58) at Kookje College in South Korea. All students were hotel management majors seeking to earn a bachelor of art degree. The experimental group (n=29) was required to watch two emotional anti-smoking advertisements while the control group (n=29) watched two logical anti-smoking advertisements. All students were required to fill out questionnaires related to process of change, depression and self-esteem. According to the ANOVA results, smoking process of change had no significant effect between the two groups on the questions pre to post. In addition, the effects of whether participants who have high self-esteem or show signs of low depression levels did not decrease smoking discouragement pre/post. Between groups ANOVAs results indicated that for depression, no significant effect was found between the two groups on the questions from pre to post. Lastly, for self-esteem, no significant effects were found between the groups on the questions from pre to post. In conclusion, emotional anti-smoking advertisements may not have a significant effect is because our participants had low self-esteem and depression levels which may have hampered positive outcomes (Seligman, 1975). Anti-smoking advertisements could psychologically trigger a panic response within the cortex of the brain which may have resulted in cognitive impairment. Participant in turn may have wanted to smoke more (Kassel, Stroud & Paronis, 2003). Lastly, as aresult of smokers potentially feeling depressed over the advertisement videos presented, participants may have wanted to smoke to inhale nicotine which can help stimulate dopamine levels and artificially trigger positive mood and feeling (Fu, Matta, Gao, Brower & Sharp,